2008
DOI: 10.1002/jpln.200700080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen supply on water‐use efficiency of higher plants

Abstract: The worldwide increase of food demand and reduced sweet‐water availability in some important food‐producing regions raised interest in more efficient water use, which has become one of the central research topics in agriculture. Improved irrigation management and reduced bare‐soil evaporation have highest priority to increase agronomic water‐use efficiency (WUE). Compared to these technical (irrigation) and basic (crop production) management options, effects of nutrient management on WUE were less frequently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 66 publications
4
41
0
2
Order By: Relevance
“…Studies comparing grassland RUE under variable N fertilizer application consistently indicated positive effects of N supply on RUE (Lauenroth et al 1978;Bai et al 2008). These findings are consistent with results from pot experiments showing that biomass water-use efficiency increases under water stress (Bacon 2004) and increases with N supply (Brueck 2008).…”
Section: Introductionsupporting
confidence: 85%
“…Studies comparing grassland RUE under variable N fertilizer application consistently indicated positive effects of N supply on RUE (Lauenroth et al 1978;Bai et al 2008). These findings are consistent with results from pot experiments showing that biomass water-use efficiency increases under water stress (Bacon 2004) and increases with N supply (Brueck 2008).…”
Section: Introductionsupporting
confidence: 85%
“…Although there has been much research on the influence of N supply on WUE, from uniform results have not always been obtained as described by Brueck (2008). There are many reports associating improvement of WUE with N supply (Heitholt, 1989; Pieterse et al, 1997Brück et al, 2001; Brueck andSenbayram, 2009;Kütük et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although much attention has been focused on the impact of fertilizer N supply on WUE, results are not necessarily consistent (Brueck, 2008). Past many researches show that an increase in N supply accompanies an increase in WUE (Heitholt, 1989;Pieterse et al, 1997;Brück et al, 2001;Kütük et al, 2004;Brueck and Senbayram, 2009).…”
mentioning
confidence: 98%
“…Based on equation (Brueck, 2008), it can be analytically calculate (equation system 3) the depth of irrigation water and nitrogen fertilizer that can be applied to ensure maximum performance. The constraints imposed for optimizing resource, including the minimum and maximum amounts actually used in this study.…”
Section: First Scenario: Lack Of Water Resources Restrictionmentioning
confidence: 99%